Giant Placental Chorioangioma with Good Perinatal Outcome: A Report of Two Cases - Somayeh Khanjani; Nazem Maedeh; Haniyeh Salehi; Zahra Sheikhsoleimani; Azam Zafarbakhsh (Case Reports in Clinical Practice, 2026)
Placental chorioangioma is the most common benign non-trophoblastic vascular tumor of the placenta. Although most lesions are small and clinically insignificant, giant chorioangiomas (>4 cm) are rare and may be associated with significant maternal and fetal complications, including polyhydramnios, fetal anemia, hydrops fetalis, growth restriction, preterm delivery, and perinatal death. We report two cases of prenatally diagnosed giant placental chorioangioma with favorable perinatal outcomes. The first patient was a 32-year-old gravida 2 para 1 woman in whom a placental mass measuring 9 × 7 × 5.5 cm was identified at 19 weeks of gestation. Serial ultrasonographic and Doppler evaluations demonstrated a vascular placental tumor consistent with chorioangioma. Mild polyhydramnios developed during follow-up; however, fetal growth, cardiac function, and middle cerebral artery peak systolic velocity remained normal. The pregnancy was managed conservatively, and a healthy neonate was delivered by cesarean section at 37 weeks of gestation. The second patient was a 23-year-old primigravida referred at 35 weeks of gestation with a 9 × 6 cm placental mass. Serial assessments showed no fetal compromise or maternal complications. She delivered a healthy 3200-g female infant vaginally at 38 weeks and 3 days. Histopathological examination confirmed the diagnosis of placental chorioangioma in both cases. Despite their large size, both tumors were associated with favorable maternal and neonatal outcomes. These cases highlight the variable clinical course of giant chorioangiomas and emphasize the importance of close antenatal surveillance using ultrasound and Doppler studies to detect potential complications. Giant placental chorioangiomas may remain clinically stable and result in successful pregnancy outcomes when carefully monitored. Prenatal ultrasonography with color Doppler plays a pivotal role in diagnosis and follow-up, while histopathological examination remains the definitive method of diagnosis.